2005
DOI: 10.1088/0967-3334/26/6/017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of tympanic membrane displacement with invasive intracranial pressure measurements

Abstract: A non-invasive method of assessing intracranial pressure (ICP) would be of benefit to patients with abnormal cerebral pathology that could give rise to changes in ICP. In particular, it would assist the regular monitoring of hydrocephalus patients. This study evaluated a technique using tympanic membrane displacement (TMD) measurements, which has been reported to provide a reliable, non-invasive measure of ICP. A group of 135 hydrocephalus patients was studied, as well as 13 patients with benign intracranial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 11 publications
1
54
0
2
Order By: Relevance
“…The median pre-intubation Glasgow Coma Scale (GCS) score of the patients was 6 (range, [3][4][5][6][7][8][9][10][11][12][13][14]. The data included daily recordings of ABP, ICP, and TCD, in a total of 66 recordings.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The median pre-intubation Glasgow Coma Scale (GCS) score of the patients was 6 (range, [3][4][5][6][7][8][9][10][11][12][13][14]. The data included daily recordings of ABP, ICP, and TCD, in a total of 66 recordings.…”
Section: Patient Populationmentioning
confidence: 99%
“…Several methods for noninvasive assessment of ICP (nICP) have been described so far: transcranial Doppler ultrasonography (TCD) to measure cerebral blood flow velocity indices 2 ; skull vibrations 3 ; brain tissue resonance 4 or transcranial time of flight 5 ; venous ophthalmodynamometry 6 ; optic nerve sheath diameter assessment (ONSD) 7 ; sensing tympanic membrane displacement (TMD) 8,9 ; otoacoustic emissions 10 ; magnetic resonance imaging to estimate intracranial compliance 11 ; ultrasound-guided eyeball compression 12 ; and recordings of visual evoked potentials. 13 These methods are better suited for one-point assessment of instant value of ICP rather than continuous monitoring.…”
mentioning
confidence: 99%
“…A recent large study by Zweifel et al [14] showed that the TCD pulsatility index for non-invasive assessments of ICP is very limited. Tympanic membrane displacement (TMD) from the stapedius reflex was shown to correlate with ICP but with a wide ICP prediction interval [15]. Another audiological approach was based on the evoked distorsion product otoacoustic emissions, which correlates with ICP [16,17], but it has not been thoroughly evaluated against invasive measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods such as transcranial Doppler (TCD) ultrasonography,[34] tympanic membrane displacement,[56] optic nerve sheath diameter,[78] and transcranial color-coded duplex sonography. [9] Noninvasive techniques lack the accuracy of their invasive counterparts thus they cannot be used as an alternative to the invasive techniques.…”
Section: Intracranial Pressure Monitoringmentioning
confidence: 99%